Strikes - "Hyman, Richard" (Fontana, 1972)
Why do industrial conflicts occur? Are their economic effects exaggerated, as many economists claim? And why are they seen as a serious social problem? Richard Hyman analyses the factors which spark off a strike, and the implications of striking for the worker, employer, trade union and society in general. He shows how sociologists can assess and interpret industrial conflict; how society's reactions to industrial disputes are generated; and the role of strikes within industry and society. The revised edition well established book looks at the effects of inflation and wage control on striking, and its incidence since 1971.
Keywords: Labour economics